1976
DOI: 10.1113/jphysiol.1976.sp011391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of various ambient temperatures and of heating and cooling the hypothalamus and cervical spinal cord on antidiuretic hormone secretion and urinary osmolality in pigs.

Abstract: SUMMARY1. Plasma ADH concentration, urinary and plasma osmolality and -haematocrit were measured in young pigs placed in cold, thermoneutral, warm and hot ambient temperatures. In some experiments a thermode placed in the hypothalamus or over the cervical spinal cord was heated or cooled at various ambient temperatures.2. Plasma ADH concentration remained at a low level (0.5-5 ,uu. ml.-') over 2 hr or 3 hr periods when the pigs were in cold, thermoneutral or warm ambient temperatures. A hot environment, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 17 publications
(19 reference statements)
0
38
0
Order By: Relevance
“…In these pigs the plasma concentration of ADH was measured in addition to the corticosteroid concentration. As can be seen in Figure 11, when the thermode was cooled the rise in corticosteroids in an ambient temperature of 43°C still occurred, but the rise in ADH which is normally seen on exposure to heat (Forsling et al, 1976) (compare Figure 10) In the present work the sensitivity of the pituitaryadrenal system of the domestic pig and the consistency of its response to disturbances in the environment of the animal has been tested.…”
Section: Effect Of Exogenious Acth On Plasma Corticosteroid Concentramentioning
confidence: 95%
See 2 more Smart Citations
“…In these pigs the plasma concentration of ADH was measured in addition to the corticosteroid concentration. As can be seen in Figure 11, when the thermode was cooled the rise in corticosteroids in an ambient temperature of 43°C still occurred, but the rise in ADH which is normally seen on exposure to heat (Forsling et al, 1976) (compare Figure 10) In the present work the sensitivity of the pituitaryadrenal system of the domestic pig and the consistency of its response to disturbances in the environment of the animal has been tested.…”
Section: Effect Of Exogenious Acth On Plasma Corticosteroid Concentramentioning
confidence: 95%
“…Figure 8 shows the results of yet another experiment in which a pig was exposed to -5°C. In this case the plasma ACTH concentrations were measured by the radioimmunoassay as well as Figure 8 Effect of a cold environment (-5 In two other piglets figures were also obtained for the plasma concentration of ADH (Forsling et al, 1976). Both the plasma concentrations of ADH and corticosteroids increased on exposure to heat ( Figure 10); the ADH retumed to the control value sooner than the plasma corticosteroids.…”
Section: Effect Of Exogenious Acth On Plasma Corticosteroid Concentramentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to hyperosmolality and hypovolemia and/or hypotension, an increase in hypothalamic temperature also stimulates VP secretion and thirst (27,28,77). Classic studies from the laboratory of Andersson (3, 4) using thermodes to locally heat and cool the preoptic-anterior hypothalamic area in the goat demonstrated that increasing and decreasing the temperature enhanced and inhibited drinking, respectively.…”
Section: Integration Of Temperature and Fluid Homeostasismentioning
confidence: 99%
“…Decreased levels of this hormone have been reported in humans (Segar & Moore, 1968) and rats (Morgan, Anderson, Ellis & Berl, 1983), whereas increased levels in unanaesthetized dogs (Sadowski et al 1972) and no consistent changes in young pigs (Forsling et al 1976) have been observed.…”
Section: Introductionmentioning
confidence: 99%